The Spectrum of β-Thalassemia Mutations in Hamadan Province, West Iran. (2nd January 2019) - Alibakhshi, Reza; Moradi, Keivan; Aznab, Mozaffar; Azimi, Azam; Shafieenia, Samaneh; Biglari, Mostafa
Abstract: β-Thalassemia (β-thal) is one of the most common hemoglobinopathies worldwide and is caused by mutations on the β-globin ( HBB ) gene. The aim of the present study was to determine the mutation spectrum of the β-globin gene in β-thal carriers who were originally from Hamadan Province, Western Iran. Two hundred and eighty-two β-thal carriers participated in the study. Amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) and direct sequencing were used for detection of different mutations. A total of 25 different mutations, including 21 β-thal mutations and four other hemoglobin (Hb) variants, in 280 β-thal carriers (99.3%) were detected in the present study. Three types of mutations including IVS-II-1 (G>A) ( HBB : c.315+1G>A) (26.24%), codons 8/9 (+G) ( HBB : c.27_28insG) (14.54%) and codons 36/37 (–T) ( HBB : c.112delT) (12.76%) accounted for more than 50.0% of the identified mutations. Moreover, IVS-I-110 (G>A) ( HBB : c.93-21G>A), codon 44 (–C) ( HBB : c.135delC) and IVS-I (25 bp deletion) ( HBB : c.93-21_del), had frequencies of 7.09, 7.09 and 5.67%, respectively. Allele frequencies of the remaining 19 mutations were less than 5.0%. This study is the first comprehensive study on a large sample size in Hamadan Province, Iran. In conclusion, the present study significantly increased the spectrum of HBB gene mutations in Hamadan Province compared with previous studies. Therefore, these results can be helpful in identifying β-thal carriers and at-risk fetuses through prenatal diagnosis (PND).